Efeitos a curto e longo prazo do fortalecimento da musculatura do assoalho pélvico com uso de cones vaginais para mulheres no período pós-menopausal com incontinência urinária de esforço: estudo randomizado controlado - Pereira, Vanessa Santos (Universidade Federal de São Carlos, 2011)
Conservative treatment is indicated by the International Continence Society as the first treatment option for women with stress urinary incontinence (SUI). Despite its wide clinical application, there is insufficient evidence to indicate the use of vaginal cones in treatment of SUI when compared with other treatment modalities. Thus, the present study investigated the short-and long-term effects of strengthening of the pelvic floor muscles with the use of vaginal cones compared to strengthening without this device and no treatment in women in post-menopausal women with SUI. Forty five volunteers were randomized in three groups: strengthening with use of vaginal cones (GCone), n = 15; strengthening without the use of vaginal cones (GS) n = 15, and the control group (CG) n = 15. The treatment consisted of 12 sessions, with two 40min sessions per week and total of six weeks of treatment. The women were evaluated before treatment, after treatment and one year after treatment for primary outcomes (urinary leakage and pelvic floor muscle pressure) and secondary outcomes (quality of life, satisfaction with treatment and continuity of exercises). It was observed a significant reduction in urinary leakage after treatment (p <0.01), which remained after one year in both GCone and GF groups. There was a significant increase of pelvic floor muscle pressure for the groups treated in the evaluation performed after treatment (p <0.01). However, it was observed a reduction in the pressure of contraction when compared values after treatment with values one year after termination for GCone (p = 0.035) and GF (p = 0.005). For the primary outcomes, the treated groups did not differ and these were statistically higher than the GC. Comparing the values of initial and final evaluations, there were improvement of quality of life for impact of urinary incontinence, limitations of daily activities, physical and social, emotional and severity measures domains (p <0.01) for the treated groups. One year after treatment, 12/14 (80%) of Gcone women and 11/13 (84.6%) of GF women declared themselves satisfied with the treatment received. In addition, 8/15 (53.3%) of GCone women and 7/13 (53.8%) GF women continued doing exercises at home without using any device. In conclusion, the strengthening with and without the use of vaginal cones promotes positive outcomes regarding urinary leakage, pelvic floor muscle pressure and quality of life in women after menopause. However, one year after the end there was a reduction in the contraction pressure without increasing urinary leakage.
Keywords: Fisioterapia; Saúde da mulher; Assoalho pélvico; Incontinência urinária de esforço; Pós-menopausa; Pelvic floor; Stress urinary incontinence; Postmenopause.; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL